1998
DOI: 10.1002/(sici)1098-2744(199806)22:2<73::aid-mc2>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of epidermal growth factor receptor ligands in tumor promoter–treated mouse epidermis and in primary mouse skin tumors induced by an initiation-promotion protocol

Abstract: Multiple epidermal growth factor receptor (EGFr) ligands have been identified, including transforming growth factor alpha (TGFalpha), heparin-binding epidermal growth factor (HB-EGF), amphiregulin (AR), and betacellulin (BTC). Previous work from our laboratory demonstrated that TGFalpha mRNA and protein are upregulated in epidermis during tumor-promoter treatment of mouse skin and in skin tumors produced by initiation-promotion regimens. The purpose of the study described here was to explore the role of other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…Previous studies have shown that the EGFR is activated (20) and the levels of its ligands (both mRNA and protein; Refs. 18,19,21) are elevated in tumor promoter-treated mouse epidermis and in skin papillomas. Through a series of experiments whereby EGFR function was modulated, we demonstrated that Stat3 activity was regulated, at least in part, by EGFR signaling during skin tumor promotion.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Previous studies have shown that the EGFR is activated (20) and the levels of its ligands (both mRNA and protein; Refs. 18,19,21) are elevated in tumor promoter-treated mouse epidermis and in skin papillomas. Through a series of experiments whereby EGFR function was modulated, we demonstrated that Stat3 activity was regulated, at least in part, by EGFR signaling during skin tumor promotion.…”
Section: Discussionmentioning
confidence: 97%
“…Our laboratory has previously shown activation of the EGFR (18,20) concomitant with an elevated expression of its ligands (18,19,21) in mouse epidermis treated with TPA. In addition, these changes are constitutive in skin papillomas generated by the two-stage DMBA-TPA regimen (20,21). Therefore, we examined whether the EGFR pathway is involved in the activation of Stat3 during tumor promotion and multistage skin carcinogenesis.…”
Section: Activation Of Stats In Mousementioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, invasion through Matrigel was also elevated in a similar manner (Supplementary Figure 2). Many growth factors (for example, EGF receptor ligands) are upregulated during tumor promotion in the mouse skin model (Rho et al, 1994;Kiguchi et al, 1998). Previous work using a human skin organ culture model demonstrated enhanced invasion of epidermal Stat3 in malignant progression of skin tumors KS Chan et al keratinocytes into the underlying dermal tissue following exposure to both EGF and HGF (Zeigler et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Several of these ligands are up-regulated during wound healing (Grotendorst et al, 1989;McCarthy et al, 1996;Stoll et al, 1997), in hyperproliferative skin conditions such as psoriasis (Elder et al, 1989;Cook et al, 1992;Downing et al, 1997; and retinoid-treated skin Varani et al, 2001), and during malignant transformation by chemical carcinogens (Kiguchi et al, 1998) or oncogenes (Dlugosz et al, 1995). Using the skin organ culture system, we have shown that the induction of HB-EGF and amphiregulin (AR) expression during wounding is strongly dependent on ErbB signaling (Stoll et al, 1997), and also on downstream signaling through the extracellular signal-regulated kinase (ERK) pathway .…”
Section: Introductionmentioning
confidence: 99%